CRITICAL EVALUATION OF THE PROPOSITION OF LAW RELATING TO THE CONSERVATION OF THE WOLF IN SPAIN AND ITS COHABITATION WITH EXTENSIVE LIVESTOCK AND THE FIGHT AGAINST THE DEMOGRAPHIC CHALLENGE - Durá Alemañ, Carlos Javier; Reyes, Zebensui Morales; Brufao Curiel, Pedro; Rodero, Jesús Agustín Pueyo; Valdemoro, Francisco Javier Zatarain; Bao, José Vicente López (Centro de Investigaciones Energéticas, Medioambientales y Tecnológicas (España), 2024)
The trend of wolves (Canis lupus) is stable or increasing across Europe. In Spain, the legal status of wolves is established according to the Duero River. North of Duero River the species is listed in the Annex V of the 1992 Habitats Directive, while south of the river is included in Annex IV. Firstly, through Order TEC/596/2019, for the fraction of the wolf population south of this river and, subsequently, with Order TED/980/2021 for the entire wolf population in Spain, wolves are included in the List of Wild Species under Special Protection Regime (hereinafter LESRPE, in Spanish). Recently, the Spanish Congress of Deputies admitted a bill presented by the Popular Parliamentary Group that seeks to remove the protection regime under the LESRPE for the wolf population fraction north of the Duero River. In this article, we carried out a critical review of such proposal. Both scientific and legal deficiencies are identified that entail, among other issues, the violation of European Union law or the absence of references to the implementation of livestock damage prevention measures, required, both at European and national level. La tendencia de las poblaciones europeas de lobo (Canis lupus) es, en general, estable o en aumento. En España, el estatus jurídico del lobo se ha dividido conforme al río Duero, considerando la fracción de la población al norte del río Duero en el Anexo V de la Directiva Hábitats de 1992, mientras que al sur del río se incluye en el Anexo IV. Primeramente, mediante la Orden TEC/596/2019, para la fracción al sur del Duero y, posteriormente, con la Orden TED/980/2021 para toda la población de lobo ibérico en España, se modificó el anexo del Real Decreto 139/2011, de 4 de febrero, para el desarrollo del Listado de Especies Silvestres en Régimen de Protección Especial (en adelante LESRPE) y del Catálogo Español de Especies Amenazadas (CEEA). Dicha Orden aprobó la inclusión de toda la población española de lobo en el LESRPE. Recientemente, el Congreso de los Diputados admitió a trámite una ...